(untitled) (Research, Society and Development, 2025)
Climate variability is a determining factor for agricultural sustainability and food security. The objective of this study was to evaluate the impact of climatic conditions on mandarin production in the Santa Rita parish, Chone canton. Two zones were distinguished: the upper zone, called "Río Santo," and the lower zone, "Río Mosquito." The research included the analysis of seven production parameters through producer surveys, complemented by the installation of meteorological stations in each zone for the daily collection of precipitation, temperature, humidity, and evapotranspiration data for seven months (January–July 2025). The data were statistically analyzed using Pearson correlation and compared with 12-year historical series from NASA (2010–2022). The results showed that the most cultivated variety was the Manabita, with average yields of 169.83 kg/m² in Río Santo and 149.18 kg/m² in Río Mosquito. Evapotranspiration and temperature were positively correlated with yield (r = 0.82 and r = 0.87, respectively), while humidity and precipitation showed negative correlations. These findings confirm that climate variability directly influences flowering and fruiting processes in mandarin, affecting yield levels in the studied areas.